Heat transfer characteristics of parallel and counter flow Microchannel heat exchangers with varying wall resistance - Maqableh, A. M.; Khadrawi, A. F.; Al-Nimr, M. A.; Ammourah, S. A.; Benim, A. C. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.